Regulation of Deoxyribonucleic Acid Replication and Cell Division in Escherichia coli B/r - Clark, D. Joseph (1968)
Synchronous cultures of Escherichia coli strain B/r were used to investigate the relationship between deoxyribonucleic acid (DNA) replication and cell division. We have determined that terminal steps in division can proceed in the absence of DNA synthesis. Inhibition of DNA replication with nalidixic acid prior to the start of a new round of replication does not stop cell division, which indicates that the start of the round is not essential in triggering cell division. Inhibition of DNA replication at any time prior to the termination of a round of replication completely blocks cell division, which suggests that there may be a link between the end of the replication cycle and the commitment of the cell to divide. Studies that use a temperature-sensitive mutant which is unable to synthesize DNA at the nonpermissive temperature are in complete agreement with those that use nalidixic acid to inhibit DNA synthesis. This adds support to the idea that the treatments employed limit their action to DNA synthesis. Investigation of minicell production indicates that the production of minicells is blocked when DNA synthesis is inhibited with nalidixic acid. Although nuclear segregation is not required for cell division, DNA synthesis is still required to trigger division. The evidence presented suggests strongly that (i) DNA synthesis is essential for cell division, (ii) the end of a round of replication triggers cell division, and (iii) there is considerable time lapse (one-half generation) between the completion of a round of DNA replication and physical separation of the cells.